Choice of injection time of conscious sedation and its impact on pain control in colonoscopy - Su, Mingli; Chen, Tingting; Zhong, Qinghua; Lin, Dezheng; Liu, Wei; Su, Yuping; Deng, Jiaxin; Zhang, Jiawei; Hu, Jiancong; Guo, Xuefeng (Frontiers in Surgery, 2022)
Purpose: The aim of this study was to identify the effect of different injection time of conscious sedation during colonoscopy procedure. Methods: In this retrospective study, the data of patients who underwent colonoscopy from June 2020 to September 2020 were assessed to investigate the effect of different injection time of sedative drugs (midazolam and dezocine). The primary endpoint was the visual analogue scale (VAS) immediately after their colonoscopy procedure to presents their pain intensity. Results: A total of 200 patients were eligible for this study. Of them, 100 received of midazolam and dezocine injection 1 minute prior to the colonoscopy procedure (the 1 Min group) and the other 100 patients received the injection 3 min prior to the procedure (the 3 Min group). The vital signs of all patients were stable except for one patient diagnosed with inflammatory bowel disease (IBD) in the 3 Min group. A transient drop of blood pressure for this patient was observed during the colonoscopy but returned to normal after general treatment. The two groups had similar cecum intubation rate (88.0% vs 89.0%, P=0.825), addition of sedative drugs during procedure (2.0% vs 5.0%, P=0.248), adequate bowel preparation (Boston bowel preparation scale ≥6, 54.0% vs 60.0%, P=0.391), and satisfaction with procedure (86.0% vs 89.0%, P=0.521), respectively. However, patients in the 3 Min group had significantly lower visual analogue scale (±standard deviation) than the 1 Min group (0.79±1.23 vs 1.21±1.38, P=0.024). Conclusion: Conscious sedation and analgesia was safe and demonstrated good pain control during colonoscopy procedure. The timing of drugs injection during conscious sedation may affect the pain control during colonoscopy procedure since 3 min prior to procedure had better analgesia outcome than 1 min.